The relationship between adequate and fair compensation, working environment and quality of work life of employee in banking industry in Malaysia - Chong, Yee Hong; Loh, Kwok Hang; Ng, Jun Jie; Yong, Shan Shan (2022)
To study the elements that affecting the quality of work life of employee in banking industry in Malaysia. To examine the relationship between adequate and fair compensation and quality of work life of employees in the banking industry in Malaysia. To examine the relationship between working environment and quality of work life of employees in the banking industry in Malaysia.